PENERAPAN PSAK 46 TENTANG PAJAK TANGGUHAN: STUDI KASUS PADA 4 PERUSAHAAN ASURANSI DI INDONESIA PERIODE 2022-2023 - Salsabilla Dinta Aulia Azzahra’; Endang Kiswara (Diponegoro Journal of Accounting, 2026)
This study was conducted in testing the application of PSAK 46 to the company’s deferred tax using a research sample in the form of company financial statements in the insurance sector. This study uses deferred tax data in the form of deferred tax assets, deferred tax liabilities, income tax expense (benefit) in the form of current and deferred taxes contained in both the financial statements, income statements and notes to the company’s financial statements.This study uses secondary data taken using the judgmental sampling method. By using a sample of 4 insurance companies listed on the Indonesia Stock Exchange with a period range of 2022-2023. The qualitative descriptive analysis method is used in conducting this research which aims to determine the application of PSAK 46 on deferred taxes to companies. The results of this study indicate that these companies have implemented deferred taxes and have a good level of compliance in terms of presentation and application of deferred taxes in the company’s financial statements in accordance with PSAK 46 of applicable tax regulations